Food Fraud Prevention - Spink, John W. (Springer, 2019)
This book is the culmination of a wide range of activities from outreach, research, and teaching. It provides a broad “education” foundation on the topics with practical application “training” to implement a practical Food Fraud Prevention Strategy, lays out an extremely interdisciplinary foundation to help address food fraud prevention, and presents a rational approach that applies sound science to evaluate the solution, understand how the countermeasures and control systems work, establish a first financial and accounting base in enterprise risk management, explore the efficiency of those activities, and then help decide on the course of action that best protects consumers. We’ve only just begun the journey to address food fraud prevention— we’re only at the starting line—getting here was the easy part, and now the hard work begins. This book is one tool for understanding a holistic and all-encompassing perspective on the multidisciplinary Food Fraud Prevention Strategy.
Introduction, Implementation, and Management